Clinical and epidemiological profile of multiple sclerosis in a reference center in the State of Bahia, Brazil Perfil clínico e epidemiológico da esclerose múltipla em um centro de referência do Estado da Bahia - Eduardo Cardoso; Thiago Fukuda; Júlio Pereira; Jamile Seixas; Rafael Miranda; Bernardo Rodrigues; Thaís Saback; Renata Andrade; Grace Cardoso; Rosa Martinez; Juliane Avena; Ailton Melo (Arquivos de Neuro-Psiquiatria)
Multiple sclerosis (MS) is an autoimmune, demyelinating and degenerative disease that affects the central nervous system. Its prevalence and clinical aspects vary according to the continent considered, being more frequent in Caucasians and young individuals aged 20 to 40 years. Epidemiological data from Brazil show that prevalence is variable, being more frequent in the Southern and Southeastern areas of the country, rather than in the Northern and Northeastern areas. The purpose of this paper is to describe MS clinical and epidemiological features in the State of Bahia, in the Brazilian Northeastern region. Thus, we held a cross-sectional study over the period from February to May, 2005, in the Multiple Sclerosis Patient Support Center ("Núcleo de Apoio aos Pacientes com Esclerose Múltipla") of Bahia, which included all patients with a diagnosis of MS seen over this period of time. A total of 121 patients were investigated, being 80.2% females (female:male ratio=4:1), with higher frequency in mulatto individuals (64%), and the relapsing-remitting type (91.3%). Most patients (68.7%) had mild MS, and blacks were prone to worse prognosis compared to other patients. A esclerose múltipla (EM) é doença auto-imune, desmielinizante e degenerativa que afeta o sistema nervoso central. Sua prevalência e seus aspectos clínicos variam de acordo com o continente estudado, sendo mais freqüente em caucasianos e indivíduos jovens entre a terceira e quarta décadas de vida. Dados epidemiológicos sobre o Brasil demonstram que a prevalência é variável, sendo mais freqüente nas regiões sul e sudeste que no norte e nordeste. O objetivo desse estudo é descrever as características clínicas e epidemiológicas da EM no Estado da Bahia, nordeste brasileiro. Assim, realizamos estudo de corte transversal durante o período de fevereiro a maio de 2005, no Núcleo de Apoio ao Pacientes com Esclerose Múltipla da Bahia, incluindo todos os pacientes consecutivos, com diagnóstico de EM, atendidos nesse período. Foi estudado um total de 121 pacientes, 80,2% do gênero feminino com uma relação de 4:1 com o gênero masculino, sendo observado maior freqüência de mulatos (64%) e da forma surto-remissão (91,3%). A maioria dos pacientes (68,7%) foi classificada como EM leve, sendo que os negros apresentaram indícios de pior prognóstico em relação aos outros pacientes.